2022
DOI: 10.3390/biomedicines10061418
|View full text |Cite
|
Sign up to set email alerts
|

Theophylline Induces Remyelination and Functional Recovery in a Mouse Model of Peripheral Neuropathy

Abstract: Charcot-Marie-Tooth disease (CMT) is a large group of inherited peripheral neuropathies that are primarily due to demyelination and/or axonal degeneration. CMT type 1A (CMT1A), which is caused by the duplication of the peripheral myelin protein 22 (PMP22) gene, is a demyelinating and the most frequent CMT subtype. Hypermyelination, demyelination, and secondary loss of large-caliber axons are hallmarks of CMT1A, and there is currently no cure and no efficient treatment to alleviate the symptoms of the disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…For example, Duman et al demonstrated that theophylline had beneficial effects on demyelination in a mouse model of peripheral neuropathy. 35 More specifically, they showed that theophylline restored demyelination by regulating the expression of sox10 and krox20. Liu et al reported that a ketogenic diet could improve remyelination by promoting Schwann cell maturation (MBP, pmp22, and sox10).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Duman et al demonstrated that theophylline had beneficial effects on demyelination in a mouse model of peripheral neuropathy. 35 More specifically, they showed that theophylline restored demyelination by regulating the expression of sox10 and krox20. Liu et al reported that a ketogenic diet could improve remyelination by promoting Schwann cell maturation (MBP, pmp22, and sox10).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with the CMT1A type, the more severe the disease, the more difficult it is to bend the instep, limiting bending and deforming the foot. These characteristics also appear in C22 mice, and the severity can be evaluated using the SFI by gait analysis [33].…”
Section: Discussionmentioning
confidence: 99%
“…HDAC2 prevents the targeting of Sox10 to the proteasome via deacetylating its negative regulator eukaryotic elongation factor 1A1 (eEF1A1) [ 75 ] and thereby promotes Sox10-mediated activation of promyelinating and myelin genes, such as Myrf and Myelin basic protein ( Mbp ) in OLs [ 94 ]. Theophylline, a potent HDAC2 activator when used at a low dose, increases Sox10 and myelin protein expression and remyelination in the mouse spinal cord after a demyelinating lesion by lysolecithin in young and old adults [ 75 ], in the mouse sciatic nerve after nerve crush injury [ 75 ] and in a mouse model of peripheral neuropathy [ 95 ]. On the other hand, co-immunoprecipitation analyses revealed that the association of HDAC1/2 with the transcription factor Yin Yang 1 (YY1) was weak in OPCs but enhanced in OLs [ 93 ].…”
Section: Roles Of Oligodendrocyte Lineage Cells In Remyelinationmentioning
confidence: 99%